TRANSLATION-THEORETICAL RESEARCH AND METHODOLOGICAL RESEARCH - Sheraliyeva, Shaxnoza (Журнал иностранных языков и лингвистики, 2023)
Our article describes in detail the basics of translation theory, the subject of research, and methods for analyzing translation theory. The importance of translation between different peoples, the concept of translation, and opinions about its types are discussed. However, various examples of translation types are given.